2017
DOI: 10.1002/term.2371
|View full text |Cite
|
Sign up to set email alerts
|

Loading of BMP‐2‐related peptide onto three‐dimensional nano‐hydroxyapatite scaffolds accelerates mineralization in critical‐sized cranial bone defects

Abstract: Extrusion free-forming, as a rapid prototyping technique, is extensively applied in fabricating ceramic material in bone tissue engineering. To improve the osteoinductivity of nano-hydroxyapatite (nHA) scaffold fabricated by extrusion free-forming, in this study, we incorporated a new peptide (P28) and optimized the superficial microstructure after shaping by controlling the sintering temperature. P28, a novel bone morphogenic protein 2 (BMP-2)-related peptide, was designed in this study. Analysis of the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 61 publications
3
43
0
1
Order By: Relevance
“…Both P24 and P28 BMP-2 mimicking peptides exhibited comparable bone formation to BMP-2 protein loaded scaffolds in vivo. [40, 41] However, in both the previous studies, large amounts of peptide of the order of 1–3 mg was loaded per scaffold to elicit bone healing, where as in our case, only ~10 μg of E7-BMP-2 peptide per scaffold was sufficient to evoke more than 60% defect closure over 8 weeks. Thus, it may be concluded that the 3D hybrid nanofiber aerogels are excellent synthetic matrices for efficient loading and delivery of osteoinductive peptides/ions necessary for cranial bone defect healing.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Both P24 and P28 BMP-2 mimicking peptides exhibited comparable bone formation to BMP-2 protein loaded scaffolds in vivo. [40, 41] However, in both the previous studies, large amounts of peptide of the order of 1–3 mg was loaded per scaffold to elicit bone healing, where as in our case, only ~10 μg of E7-BMP-2 peptide per scaffold was sufficient to evoke more than 60% defect closure over 8 weeks. Thus, it may be concluded that the 3D hybrid nanofiber aerogels are excellent synthetic matrices for efficient loading and delivery of osteoinductive peptides/ions necessary for cranial bone defect healing.…”
Section: Discussionmentioning
confidence: 58%
“…[39, 40] Such peptides presented on 3D alginate hydrogels scaffolds by chemical conjugation induced osteogenic differentiation of osteoprogenitor cells in vitro . [11] Particularly, the engineering of peptide with the heptaglutamate E7 domain to confer enhanced calcium binding properties as necessary to deposit bone mineral led us to choose this peptide for our study.…”
Section: Discussionmentioning
confidence: 99%
“…We took a step further by synthesizing a new bioactive P4 analog, namely P28, which is constituted of S[PO4]DDDDDDDKIPKASSVPTELSAISTLYL. We confirmed its bioactivity in promoting repair of calvarial defects in a rat model . Different from P4, P28 has a short block of seven aspartic acids (Ds) and one phosphorylated serine, both of which are added to the N‐terminus of P4.…”
Section: Introductionmentioning
confidence: 52%
“…The novel BMP2‐mimicking peptide P28 was derived from the nuclear domain of BMP2 . In addition, it has two distinct structural elements: seven aspartic acids and phosphorylated serine.…”
Section: Discussionmentioning
confidence: 99%
“…After implantation, CS can control the release rate of BMP-2 by adjusting the degradation rate and assist the BMP-2 to function in surgical prostheses. Till now, there have been some reports that the HA/CS/BMP-2 scaffolds or microspheres were prepared to accelerate bone healing [12][13][14][15] , but those materials often have poor mechanical properties, and their application is limited, especially applications for reparation of load-bearing bone tissues. Up to now, there has been no reports of preparing BMP-2/CS/HA/TiO 2 coatings on the surface of Ti implant.…”
Section: Introductionmentioning
confidence: 99%